Postactivation potentiation of bench press throw performance using velocity-based conditioning protocols with low and moderate loads - Tsoukos, A.; Brown, L. E.; Veligekas, P.; Terzis, G.; Bogdanis, G. C. (Journal of Human Kinetics, 2019)
This study examined the acute effects of the bench press exercise with low and moderate loads as well as with two predetermined movement velocity loss percentages on bench press throw performance and surface electromyographic (sEMG) activity. Ten trained men completed 5 main trials in randomized and counterbalanced order one week apart. Mean propulsive velocity (MPV), peak velocity (PV) and sEMG activity of prime movers were evaluated before and periodically for 12 minutes of recovery under five conditions: using loads of 40 or 60% of 1 RM, until mean velocity dropped to 90 or 70%, as well as a control condition (CTRL). MPV and PV were increased 4-12 min into recovery by 4.5-6.8% only after the 60%1RM condition during which velocity dropped to 90% and total exercise volume was the lowest of all conditions (p < 0.01, Hedges` g = 0.8-1.7). When peak individual responses were calculated irrespective of time, MPV was increased by 9.2 ± 4.4 (p < 0.001, Hedges` g = 1.0) and 6.1 ± 3.6% (p < 0.001, Hedges` g = 0.7) under the two conditions with the lowest total exercise volume irrespective of the load, i.e. under the conditions of 40 and 60% 1RM where velocity was allowed to drop to 90%. sEMG activity of the triceps was significantly greater when peak individual responses were taken into account only under the 60%1RM condition when velocity dropped to 90% (p < 0.05, Hedges` g = 0.4). This study showed that potentiation may be maximized by taking into account individual fatigue profiles using velocity-based training.